Monetary policy without interest rates. Evidence from France's Golden Age (1948-1973) using a narrative approach - Eric Monnet (European Historical Economics Society (EHES), 2012)
Central banking in France from 1948 to 1973 was a paradigmatic example of an unconventional policy relying on quantities rather than on interest rates. Usual SVAR find no effect of policy shocks and support the common view that monetary policy was ineffective over this period. I argue that only a narrative approach is able to account for the peculiarity and complexity of quantitative controls on money and credit. Using archival evidence, I measure monetary policy stance with a dummy variable denoting restrictive episodes. Impulse response functions then show standard patterns; monetary policy shocks have a strong and long lasting effect. These results offer a revisionist account of postwar monetary policy under Bretton Woods and before the Great Inflation. They also suggest that quantities of money and credit can play a greater role than their prices in the adjustment process of the economy.
Keywords: N14; E31; E32; E51; E52; E58; 330; monetary policy; credit controls; VAR; narrative approach; liquidity puzzle; Banque de France; Bretton Woods